Balancing Development and Community Rights: Legal and Policy Frameworks for Land Conflict Resolution in Batam, Indonesia - Tampubolon, Sahat Maruli Tua; Lagat Paroha Patar Siadari; Ramon Nofrial; Erniyanti; Soerya Respationo (Enigma in Law, 2024)
The rapid development of Batam, Indonesia, as a Special Economic Zone (SEZ) has led to significant land conflicts between the state, developers, and local communities. The existing legal and policy frameworks have been criticized for prioritizing economic growth over community rights, leading to forced evictions, inadequate compensation, and social unrest. This study aims to analyze the legal and policy frameworks governing land conflict resolution in Batam and propose recommendations for balancing development and community rights. The research employs a qualitative approach, combining legal and policy analysis with empirical data collected through interviews with key stakeholders, including government officials, community leaders, and legal experts. The study examines relevant laws, regulations, and policies related to land acquisition, compensation, and dispute resolution in Batam. The findings reveal several shortcomings in the current legal and policy frameworks, including a lack of transparency and participation in decision-making processes, inadequate compensation mechanisms, and limited access to justice for affected communities. The study also highlights the power imbalance between the state, developers, and communities, which often leads to the marginalization of community rights. The study concludes that balancing development and community rights in Batam requires a comprehensive reform of the legal and policy frameworks. The recommendations include strengthening community participation in decision-making processes, ensuring fair and adequate compensation, and improving access to justice for affected communities. The study also emphasizes the need for greater transparency and accountability in land acquisition and development processes.